Lexical Cohesion in Maher Zain’s Forgive Me Album: A Discourse Analysis - Bella Puspita; Rulik Setiani (English Education Department at FKIP Nommensen University, 2026)
This study investigates lexical cohesion in four selected song lyrics from Maher Zain's second studio album Forgive Me (2012): Forgive Me, I Love You So, Number One for Me, and My Little Girl. Adopting Halliday & Hasan (1976) lexical cohesion framework, which classifies lexical cohesion into reiteration and collocation, as the theoretical basis, this study identifies seven sub-types of lexical cohesion as adopted in subsequent linguistic research: repetition, synonym, antonym, superordinate, meronym, hyponym, and collocation. The data source of this study are the written lyrics of the four selected songs, obtained from official lyric publications. Data were collected through systematic documentation by reading each lyric carefully and identifying all lexical items that demonstrate cohesive relations. The data were analyzed following Creswell & Creswell (2017) qualitative analysis steps: organizing the data, reading through all data, coding each lexical item by its cohesion subtype, generating categories, and reporting findings. The validity of the analysis was ensured through careful re-reading and cross-checking of each datum against the theoretical criteria established by (Halliday & Hasan, 1976). The analysis identified 238 lexical cohesion items. Collocation emerged as the most dominant type with 71 items (29.8%), followed by repetition (56 items; 23.5%), synonym (28 items; 11.8%), hyponym (26 items; 10.9%), antonym (23 items; 9.7%), meronym (19 items; 8.0%), and superordinate (15 items; 6.3%). Among the four songs, My Little Girl yields the highest number of lexical cohesion items (66 items; 27.7%). The dominance of collocation reflects the formulaic devotional register characteristic of Islamic nasheed, distinguishing Maher Zain’s lyrics from mainstream pop music where repetition typically dominates. These findings confirm that Maher Zain’s song lyrics operate as linguistically cohesive discourses that employ diverse lexical mechanisms to achieve semantic unity and emotional impact.